Contribution to the Study of the Photocatalytic Efficacy of Some Metal Oxides in the Removal of Organic Pollutants - باهي فردوس – ابتهال رزازقة (university of eloued جامعة الوادي, 2024)
يواجه العالم ارتفاع مستويات التلوث، وخاصة التلوث العضوي الناجم عن الأنشطة الصناعية والزراعية. وتشكل هذه الملوثات تهديدا كبيرا للبيئة والصحة العامة، مما دفع العلماء إلى البحث عن حلول فعالة لإزالتها. يهدف هذا البحث إلى المساهمة في فهم فعالية الأكسدة التحفيزية الضوئية باستخدام أكاسيد فلزية محددة وهي ثاني أكسيد التيتانيوم (TiO2) وثاني أكسيد المنغنيز (MnO2). في معالجة الملوثات العضوية. ركزت الدراسة على تحلل أزرق الميثيلين، وهو ملوث بيئي شائع، باستخدام القياس الطيفي للأشعة فوق البنفسجية. أظهرت النتائج التفوق الملحوظ لأداء TiO2 في الحياد الوسائط، نجحت في تحليل 49.64% من الملوثات خلال ساعة من التشعيع. وبالمقارنة، أظهر MnO2 كفاءة أقل في ظل نفس الظروف، حيث حقق معدل تحلل قدره 46.3% بعد ساعة و30 دقيقة. تم تحديد التركيزات المثالية التي تؤدي إلى أعلى معدلات التفاعل في كلتا الحالتين لتكون 8 جزء في المليون للملوث. اتبع النموذج الحركي معدل الدرجة الأولى الزائف في كلتا الحالتين. The world is grappling with rising levels of pollution, particularly organic pollution stemming from industrial and agricultural activities. These pollutants pose a significantthreat to the environment and public health, prompting scientists to seek effective solutions for their removal. This research aims to contribute to understanding the effectiveness of photocatalytic oxidation using specific metal oxides, titanium dioxide (TiO2 ) and manganese dioxide (MnO2 ), in treating organic pollutants. The study focused on the degradation of methylene blue, a common environmental pollutant, using UV-Vis spectrophotometry. The results demonstrated the remarkable superiority of TiO2 performance in neutral media, successfully degrading 49.64% of the pollutant within an hour of irradiation. In comparison, MnO2 exhibited lower efficiency under the same conditions, achieving a 46.3% degradation rate after one hour and 30 minutes. The optimal concentrations leading to the highest reaction rates in both cases were determined to be 8 ppm for the pollutant. The kinetic model followed a pseudo-first-order rate in both case
مدكرة ماستر كيمياء
Keywords: التلوث، التحفيز الضوئي، أكاسيد المعادن، أزرق الميثيلين، التحلل; pollution; photocatalytic; metal oxides; methylene blue; degradation..